2006
DOI: 10.1080/17457300500172941
|View full text |Cite
|
Sign up to set email alerts
|

Drowning – a major but neglected child health problem in rural Bangladesh: implications for low income countries

Abstract: This study was intended to estimate the magnitude and explore the determinants of childhood drowning in rural Bangladesh. A cross-sectional survey as well as a population-based case - control study was conducted. By multistage cluster sampling 51 147 children aged 1 - 4 years were identified from 108 827 rural households. All drownings in children aged 1 - 4 years in the preceding 5 years were identified and recruited as cases and two living children of the same age group were selected from the same localities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
69
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 20 publications
10
69
4
Order By: Relevance
“…After excluding bathtub drowning deaths to analyze drownings possibly related to swimming and/or water safety skills, men and women from rural areas had a significantly higher risk of drowning compared with their non-rural counterparts. Previous studies have found rural residency to be associated with an increased risk of drowning, but the majority of these studies were restricted to pediatric drowning deaths (Fang et al, 2007;Hammig & Weatherly, 2003;Kim, Ozegovic, & Voaklander, 2012;Ma et al, 2010;Rahman et al, 2006;Svenson et al, 1996;World Health Organization, 2012). Our study is unique in that we included all ages of drowning victims.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding bathtub drowning deaths to analyze drownings possibly related to swimming and/or water safety skills, men and women from rural areas had a significantly higher risk of drowning compared with their non-rural counterparts. Previous studies have found rural residency to be associated with an increased risk of drowning, but the majority of these studies were restricted to pediatric drowning deaths (Fang et al, 2007;Hammig & Weatherly, 2003;Kim, Ozegovic, & Voaklander, 2012;Ma et al, 2010;Rahman et al, 2006;Svenson et al, 1996;World Health Organization, 2012). Our study is unique in that we included all ages of drowning victims.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from the U.S., Australia, and Bangladesh found the highest rates of drowning among children aged 1-4 (Mackie, 1999;Quan et al, 1989;Rahman et al, 2006). More recent data from China found that children aged 5-14 had the highest risk of drowning (Fang et al, 2007).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Drowning rates are highest among children and in rural areas (Fang et al, 2007;Quan & Cummings, 2003;Rahman et al, 2006;Sitthi-amorn et al, 2006). Providing swimming lessons is an important strategy to prevent childhood drowning (Brenner et al, 2009;Hyder, Borse et al, 2008;McIntosh, 2009;Rahman et al, 2010;World Health Organization, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Drowning is one of the most common causes of death among young children in developing countries in Asia, including Thailand (Fang et al, 2007;Hyder, Wali, Fishman, & Schenk, 2008;Linnan et al, 2007;Rahman, Giashuddin, Svanstrom, & Rahman, 2006;Sitthi-amorn et al, 2006). In 1999, a study of unintentional injury death among children aged 2-16 years in Thailand showed that 35% of deaths were due to drowning (13.1/100,000; Kozik et al, 1999).…”
mentioning
confidence: 99%